The Effect of Suture-Mediated Closure Device on Hemostasis in Patients after Transfemoral Cardiac Procedures - an Evidence-Based Practice - Arif Nur Akhmad; Ching-I Liou; Li-Wen Su; Fifi Alviana; Candra Dewi Rahayu (Indonesian Journal of Global Health Research, 2021)
Patients who used manual compression after transfemoral cardiac procedures could suffer from several problems. The suture-mediated closure device may be proven as an effective alternative, offering earlier sheath removal, and potentially a reduction in vascular complications. The aim of this study was to discover empirical bases and clinical application of suture-mediated closure devices on hemostasis in patients after transfemoral cardiac procedures. This study was applied on evidence-based practice in the clinical setting. The search process for evidence-based practices used 3 databases such as MEDLINE, PubMed, and Web of Science, obtaining 14 studies published between 2000 and 2016. The studies selected were assessed by two reviewers for their methodological quality and level of evidence prior to inclusion in the review. Research subjects were patients at the age of ≥ 20 years old who suffered from coronary artery disease and required transfemoral cardiac procedures. This study was implemented in a Medical Intensive Care Unit, Changhua Christian Hospital. The hemostasis status was evaluated based on two categories of, bleeding or not bleeding. Six patients were included in this study. Most of the patients were male with average age of 69.33 ± 11.70 years old. Hypertension, diabetes mellitus, and hyperlipidemia were their common history of diseases. Based on the evaluation outcome, five patients showed hemostasis status and only one patient had bleeding after the compression procedures. This study concludes that the suture-mediated closure device is effective for patients after transfemoral cardiac procedures to reach hemostasis status quickly based on clinical evaluation.